The Profile of the Protagonists of Workplace Bullying in Education- Emotions - Γεράκη Ακριβούλα; Καλλιατάκη Ελένη (Education Sciences, 2024)
Bullying is a global phenomenon of research interest. The present research aims to give voice to the protagonists. Particular emphasis is placed on the witness or observer of workplace bullying, their emotions and their role. Therefore, the technique of semi-structured interviews was chosen using the qualitative methodology to collect data and thematic analysis to investigate it. The sample consisted of twenty (20) teachers from different schools of N. Heraklion, Crete. The results showed that "bullying" as a phenomenon prevails in education. Numerous factors influence and influence its manifestation: working conditions etc.The victim's profile mainly recognizes teachers who differ for some characteristic element (little experience in schools etc) and the perpetrator's profile: “teachers leaders”, the “new teachers” and an informal group. Three categories fit the observer profile of the observer: the active, the passive and the seemingly apathetic. The dynamic interaction can determine the course of evolution of the phenomenon .